2019
DOI: 10.21106/ijma.302
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Opportunistic Infections in HIV Infected Patients on Treatment in Accredited HIV Treatment Centers in Cameroon

Abstract: Background: The African continent accounts for over 70% of people infected with Human Immunodeficiency Virus (HIV). The HIV sero-prevalence rate in Africa is estimated at 4.3%. In developed countries, such as France, pneumocystis is indicative of AIDS in 30% of patients; however, in Africa, pulmonary tuberculosis (TB) is the most-documented opportunistic infection (OI) and the leading cause of death in HIV-infected patients. In 2016, Cameroon had 32,000 new cases of OI and 29,000 deaths as a result of these in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…This corroborates WHO reports that places Cameroon among the rst 30 countries with a high burden of HIV/TB coinfection [24]. In another study carried out in 12 HIV treatment centers in and Douala, showed that TB was the second most common opportunistic infection (20%) after shingles (25%) [25]. Correspondingly, retrospective studies conducted between 2010-2017 by [32][33][34].…”
Section: Discussionsupporting
confidence: 84%
“…This corroborates WHO reports that places Cameroon among the rst 30 countries with a high burden of HIV/TB coinfection [24]. In another study carried out in 12 HIV treatment centers in and Douala, showed that TB was the second most common opportunistic infection (20%) after shingles (25%) [25]. Correspondingly, retrospective studies conducted between 2010-2017 by [32][33][34].…”
Section: Discussionsupporting
confidence: 84%
“…HIV causes immunodepression by depleting CD4 cells, thus reducing the capacity of the organism to defend against bacterial, fungal, parasitic, and viral infections such as COVID-19 [20,22]. This vulnerability to infection is greater when the immunodepression is severe and the patient is not on ART making the patient at risk of opportunistic infections [23,24]. The presence of 38 million people worldwide with HIV during this period of COVID-19, could therefore be challenging for health systems worldwide as more aggressive preventive and therapeutic measures might be needed for this population.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for these discordant findings is the incidence of tuberculosis in both countries. The incidence of tuberculosis in Africa is 276 cases per 100,000 inhabitants, while in Peru 119 cases per 100,000 inhabitants have been reported [28].…”
Section: Discussionmentioning
confidence: 99%